Interface tenons en fibres et matériaux de reconstitution : revue de la littérature - ALAMEDDINE, Rayanne (International Arab Journal of Dentistry (IAJD), 2011)
The use of fiber-reinforced posts is nowadays a recent solution for the restoration of endodontically treated teeth. Has it become an alternative to traditional metallic post and core? Current data suggest that there is an adhesion problem in the interface post/ composite core and the ongoing studies focus on the improvement of this chemical and/or mechanical bond. Several factors play an important role in this adhesion, such as the surface treatment of the fiber-reinforced post and the type of composite used.